MOTIVASI SEMANGAT BERWIRAUSAHA GENERASI MUDA KHUSUSNYA DI KALANGAN SISWA SMKS AL-QUDSY CIBATU KABUPATEN GARUT - Sugiat, Jajang; Rusdian, Suca (EJOIN : Jurnal Pengabdian Masyarakat, 2023)
Opportunities for the younger generation to work in government offices or companies are dwindling due to increasingly fierce competition in formal sector jobs. On the other hand, the younger generation does not want to become an entrepreneur and earn work and money independently. The aim of the Community Service (PKM) program is to prepare the productive young generation to become more motivated, have passion, strong character and profits in entrepreneurship. To achieve this goal, students at Al-Qudsy Cibatu Vocational School, Cibatu Regency, Garut Regency were given knowledge and motivation about entrepreneurship. The results of the activity showed that students had high interest and motivation for entrepreneurship, but students still felt confused and afraid to start. Apart from that, the role of support from school institutions and families is still minimal, so in developing young entrepreneurs all parties, including families, communities, educational institutions, and the government and private sectors must play a role.